The Relationship between Students Knowladge and personal hygiene with incidence of diarrhea in students at SMP Negeri - Hibban D. I. Azzufar; Windi Wulandari; Mitoriana Porusia (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
Diarrhea was a serious health problem for all age groups, especially among school-aged children. The Ministry of Health reported in 2025 that diarrhea ranked second among diseases with the highest potential for outbreaks in Indonesia, with 2,046,806 cases recorded as of mid-2025. The number of diarrhea cases in Surakarta increased from 7,209 cases in 2023 to 11,434 cases in 2024. This study aimed to investigate the relationship between student knowledge and personal hygiene behavior, as well as the incidence of diarrhea, among students of SMP Negeri Surakarta. This study employed a quantitative method with a cross-sectional approach and a proportional sampling technique, involving 184 respondents from grades VII, VIII, and IX. Data analysis was conducted using both univariate and bivariate analyses, including the Chi-Square test. The results indicated a significant relationship between student knowledge (p-value = 0.000) and personal hygiene behavior (p-value = 0.000) with the incidence of diarrhea among students of SMP Negeri Surakarta. This study concluded that personal hygiene knowledge and behavior had a significant impact on the incidence of diarrheal diseases. However, other factors also contributed to the spread of diarrheal diseases, including environmental sanitation, water hygiene, and disease transmission through canteen handlers. From this matter, it is expected that the school also plays an active role in continuous disease prevention efforts, both through theoretical education and practical implementation, as well as by improving supporting facilities to provide a safe, healthy, and comfortable environment for students.